Computational investigation on structural and functional impact of oncogenes and tumor suppressor genes on cancer - Ceesay, Abdoulie K. (My University, 2021)
Within the sequence of the whole genome, it is known that 99.9% of human genome is similar, whilst our difference lies in just 0.1%. Among these minor dissimilarities, the most common type of genetic variations that occurs in a population is SNP, which arises due to nucleotide substitution in a protein sequence that leads to protein destabilization, alteration in dynamics and other physio-chemical properties’ distortions. While causing variations, they are equally responsible for our difference in the way we respond to a treatment or a disease including various cancer types. There are two types of SNPs; synonymous single nucleotide polymorphism (sSNP) and non-synonymous single nucleotide polymorphism (nsSNP). sSNP occur in the gene coding region without causing a change in the encoded amino acid, while nsSNP is deleterious due to its replacement of a nucleotide residue in the gene sequence that results in a change in the encoded amino acid. Predicting the effects of cancer related nsSNPs on protein stability, function and dynamics is important due to the significance of phenotype-genotype association of cancer. In this thesis, human variation datasets for 5 oncogenes (ONGs) (AKT1, ALK, ERBB2, KRAS, BRAF) and 5 Tumor Suppressor Genes (TSGs) (ESR1, CASP8, TET2, PALB2, PTEN) were retrieved from ClinVar to study the implications of nsSNPs. To this end, bioinformatics tools were used to differentiate deleterious variations from neutral and benign. The functional impact of the variations was also examined using available computational tools such as sequence-homology based, supervised learning methods, protein sequence and structure–based tools, consensusbased tools and methods using evolutionary conservation analysis. Obtained results can shed light to the future research in order to pave new frontiers in cancer therapies.

Tüm genom dizisi içinde, insan genomunun %99.9'unun benzer olduğu bilinirken, farklılıklarımız sadece kalan %0.1'den kaynaklanmaktadır. Bu küçük farklılıklar, bir protein dizisindeki nükleotid değişimi nedeniyle ortaya çıkan tek nükleotid polimorfizmi (SNP) sebebiyle proteinlerde stabilizasyon kaybına, dinamiklerinde değişikliklere ve diğer fizyo-kimyasal özelliklerde bozulmalara yol açan ve bir popülasyonda meydana gelen en yaygın genetik varyasyon türü’dür. Varyasyonlar çeşitli kanser türleri neden olurken, bir tedaviye veya bir hastalığa yanıt verme şeklimizdeki farklılığımızdan yüksek derecede sorumludurlar. İki tür SNP vardır; eşanlamlı tek nükleotid polimorfizmi (sSNP) ve eşanlamlı olmayan tek nükleotid polimorfizmi (nsSNP). sSNP, kodlanmış amino asitte bir değişikliğe neden olmadan gen kodlama bölgesinde meydana gelirken, nsSNP, gen kalıntısının içerisi bir nucleotid değişiklik nedeniyle başka amino asit ile sonuçlanan gen dizi olması nedeniyle zararlıdır. Kansere bağlı nsSNP'lerin protein stabilitesi, fonksiyonu ve dinamikleri üzerindeki etkilerini tahmin etmek, kanserin fenotip-genotip ilişkisinin önemi nedeniyle önemlidir. Bu çalışmada, 5 ONG (AKT1, ALK, ERBB2, KRAS, BRAF) ve 5 TSG (ESR1, CASP8, TET2, PALB2, PTEN) için varyasyon veri kümeleri, nsSNP'lerin etkilerini incelemek için ClinVar'dan elde edilmiştir. Zararlı varyasyonların nötr ve tehlikesiz olanlardan ayırt etmek için biyoinformatik araçlar kullanılmıştır. Varyasyonların işlevsel etkilerini incelemek için dizi-homoloji tabanlı yöntemler, denetimli öğrenme yöntemleri, protein dizilimi ve yapı tabanlı araçlar, ve evrimsel korunma analizi kullanan yöntemler gibi mevcut hesaplama araçları kullanılarak incelenmiştir. Elde edilen sonuçlar, kanser tedavilerinde yeni ufuklar açmak için gelecekteki araştırmalara ışık tutabilecektir.
Onkojenlerin ve tümör baskılayıcı genlerin kanserine yapısal ve fonksiyonel etkisi üzerinde hesapsal incelemesi
Keywords: Bioengineering; Biyomühendislik; GENES ONKOJEN; ONCOGENES; TUMOR SUPPRESSOR; TÜMÖR BASKILAYICI